Analisis Kelayakan Amenitas Pariwisata pada Ruang dan CHSE di Taman Hutan Raya Balas Klumprik Surabaya - Revani Fatma Vira Pratama; Garsione Agni Andrea (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the feasibility of tourism amenities and the implementation of cleanliness aspects based on the CHSE (Cleanliness, Health, Safety, and Environmental Sustainability) principle at Balas Klumprik Forest Park, Surabaya. This research employs a descriptive qualitative approach, with data collected through field observation, in-depth interviews with the site manager, and documentation. Informants were determined purposively, while data were analyzed through data reduction, data display, and conclusion drawing. The results show that the gazebo is the amenity that best meets the feasibility indicators due to its clean, shaded condition and strategic location. The parking area is fairly feasible, although it still lacks a dedicated space for persons with disabilities, adequate night-time lighting, and clear directional signage. The toilets and prayer room are generally usable but do not yet fully meet feasibility standards, particularly regarding lighting, ventilation, and the tidiness of prayer equipment. Waste bins are available and emptied regularly, yet an on-site waste-sorting system has not been implemented. Overall, the amenities at Balas Klumprik Forest Park can be categorized as fairly feasible, although continuous improvement is required to optimize comfort, cleanliness, accessibility, and service quality for visitors.